Wind-turbine studies: the power augmentation of flexible sail systems - Fleming, P. D. (Cranfield University, 1984)
The origin of the wind-turbine is discussed and its subsequent development reviewed. Various types of sail wind-turbine are described and their advantages and different types detailed. Their appropriateness for driving water pumps in developed, as well as in developing, countries is examined and their benefits for rural communities of less developed countries outlined. The theoretical analysis of the behaviours of both propeller-type wind-turbines and of two-dimensional yacht sails are reviewed and their possible notifications to describe the performances of flexible-sail wind-turbines discussed. A novel, wind-turbine recorded. variable sail profile, vertical-axis Savonius has been developed and its power characteristics Self-regulating peristaltic displacement pumps are proposed to be driven by the horizontal or vertical-axis wind-turbines and their operating characteristics are described. A theoretical analysis relating the torque characteristic of the wind-turbine to that of the pump is outlined. Data are presented for the power augmentation of a horizontal-axis, flexible-sail type wind-turbine, using a shroud, tip-fins and centre-bodies. Considerable power enhancements are achievable using the basic, cheap wind-turbine power augmentors tested in this investigation.